Pengembangan Instrumen Pengukuran Iklim Emosi dan Sikap pada Lingkungan Pembelajaran IPA - Hasna Rashifah; Yuli Rahmawati; Riyadi (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to enrich the discussion of the component of developing instrument as a realization of student reflection on their learning environment, and as an evaluation by researchers, teachers, and principals to increase students’ motivation and achievement. The approach of the research is a quantitative research with developing the instrument method. The research is conduct on 1.067 students of public middle school in Jakarta. The result demonstrate that the instrument that developed and validated from the instrument of Classroom Emotional Climate (CEC) and the instrument of Test Of Science-Related Attitudes (TOSRA) have eight dimensions are, collaboration, motivation, care, clarity, attitude to scientific inquiry, enjoyment of lessons, adoption of scientific attitudes, and sosial implications of science, used LISREL to test Confirmatory Factor Analysis are 37 items. The further analysis use Rasch Fit Item value is 36 items and 589 person, have five items level of difficulty and person abilities are also clustered into five levels. Besides that, Cronbach's alpha value is 0.92, Person reliability is 0.88 and item reliability is 0.99, shows that the instrument results is reliabel, therefore able to use.